Phenotypic and Molecular Characterization of Most Prevalent Eimeria Species of Dairy Cattle from Indian Subtropical Region - Kumar , Pradeep (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A total of 2469 faecal samples were examined from 12 different villages in Mathura district of Uttar Pradesh to determine the presence  and to conduct morphological and molecular characterization of Eimeria species. Morphological characterizations were performed  by the faecal flotation method. The analytic survey revealed that the overall prevalence of Eimeria species in dairy cattle was 11.05%  (273/2469). A total of nine Eimeria species were identified. E. zuernii and E. bovis species were reported in a maximum number of dairy  cattle with a prevalence rate of 6.95% and 5.49%, respectively. The internal transcribed spacer-1(ITS-1) region of the ribosomal RNA  genes of E. bovis and E. zuernii, were amplified, sequenced and studied in the current work to determine their evolutionary relationships.  Pair-wise comparison showed over 90% homology between sequences from the same species. Furthermore, species-specific PCR tests  based on amplification of the ITS-1 region were developed to differentiate between E. zuernii and E. bovis. The ITS-1 region of each  Eimeria species displayed enough interspecies sequence variation to create primer sets that specifically amplified the target species.  This PCR method demonstrated greater sensitivity than traditional methods for identifying and distinguishing between Eimeria species.  This marks the first genomic-level attempt to identify two Eimeria parasites in cattle, potentially offering valuable tools for the diagnosis  and study of cattle coccidiosis.
Keywords: Cattle; DNA; Eimeria; ITS-1; PCR; Ribosomal RNA genes